RETRACTED ARTICLE: The Prevention and Control Model for Opisthorchiasis in Chaiyaphum Province - Ronyut, Wanida; Kachaiyaphum , Prasit (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2024)
This research aimed to develop a model for preventing and controlling opisthorchiasis in Chaiyaphum Province, Thailand. The objectives include: 1) investigating factors related to the prevention and control of opisthorchiasis, 2) developing a prevention and control model, and 3) evaluating the outcomes of the developed prevention and control model. The research instruments used to collect and analyze the data comprise: 1) a high-quality questionnaire with a reliability coefficient of 0.75, covering personal data, family and friends, community, and prevalence. Binary logistic regression statistics were used to analyze the relationship between these factors and opisthorchiasis, 2) a set of activities was developed according to the health beliefs and strategies roadmap, under the collaboration of the community and local units with a focus on constructed validity, 3) the outcomes were evaluated by examining statistically significant differences between the control and experimental groups. This evaluation utilized a questionnaire on knowledge, perception, and behavior, with confidence coefficients ranging between 0.75 and 0.88. The results showed that factors related to opisthorchiasis prevalence were significantly correlated with the behaviors of consuming raw fish (Koi-Pla) (p < 0.01) and perceiving the risk of the disease (p < 0.05). After the intervention, both the experimental and control groups revealed a statistically significant reduction in the prevalence rate of liver fluke infection by 7.03% and 22.83%, respectively (p < 0.01). This study suggests that knowledge-sharing activities, raising awareness through easily understandable media, combining human communication, providing feedback, and keeping the community informed are all beneficial. Moreover, it is recommended that local government policies in the area should be implemented consistently and earnestly, and the developed model should be applied in other regions for practical and continuous improvement.